Comprehensive study of the underground hydrogen storage potential in the depleted offshore Tapti-gas field. (19th April 2023) - Kiran, Raj; Upadhyay, Rajeev; Rajak, Vinay Kumar; Gupta, Saurabh Datta; Pama, Harharjot
Abstract: Hydrogen is becoming an alternative for conventional energy sources due to absence of any Greenhouse Gases (GHG) emissions during its usage. Geological storage of hydrogen will be potential solution for dealing with large volume requirement to manage uninterrupted Hydrogen supply-chain. Geological Storages such as depleted reservoirs, aquifers and salt caverns offer great potential option for underground hydrogen storage (UHS). There are several depleted gas fields in India. One of such field is located in Tapti-Daman formation. A comprehensive study is conducted to assess the possibility of hydrogen storage in this Indian field which is first of its kind. The geological characteristic of this site is assessed for its viability for storage. Additionally, several aspects including storage capacity, sealability, chemical and micro-biological stability, reservoir simulation, and production viability are assessed using various analytical and numerical models. The qualitative analysis of the Tapti-gas field suggests that the integrity of the storage site will be intact due to existing anticlinal four-way closed structure. The chemical and micro-biological losses are minimal and will not lead to major loss of hydrogen over time. The reservoir modeling results show that optimum gas production-injection scheme needs to be engineered to maintain the required reservoir pressure level in the Tapti-gas field. Also, the deliverability of the various seasonal storage time show that 80 days production scheme will be suitable for efficient operation in this field. Finally, a synergistic scheme to enable green energy production, storage, and transportation is proposed via implementation of UHS in the offshore Tapti-gas field. Highlights: Holistic investigation of combined reservoir and geochemical modeling required for assessing the feasiblility of UHS. Injection and production scheduling is required for better utilization of seasonal hydrogen storage and production. Out of detrital and authigenic components, detrital component has significant impact on geochemical inverstigation. Production and injection rate impacts reservoir pressure. First prospect study for Offshore Indian depleted gas field for UHS purpose.